The Role of School Principals in Creating Multicultural Education in the School Employee Environment: Peran Kepala Sekolah Dalam Menciptakan Pendidikan Multikultural Di Lingkungan Karyawan Sekolah - Desika Handayani; Muhammad Farouk Albakhar Anshori; Sefti Triani; Nurlaili (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
School principals have a strategic role in creating an inclusive educational environment, especially in supporting the implementation of multicultural education among school employees. This research aims to analyze the role of school principals in building a positive and inclusive school environment, by involving all employees. The success of multicultural education is very dependent on the leadership of the school principal. The research method uses a literature review, by analyzing literature related to multicultural education practices. The research results show that school principals play a key role in implementing multicultural principles through policies and programs that support cultural diversity. They need to design organized strategies, provide relevant training, and create a tolerant work environment. To ensure multicultural values ​​are implemented effectively, school principals must also carry out routine supervision and evaluation, and ensure that every employee feels valued and involved in the educational process.